Clinical Indications of Pravala panchamrita rasa - An experiential and scientific view - Shripathi , Acharya G; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2020)
Introduction- Herbo mineral formulations are widely practiced in modern India. Mostly chronic and non communicable disorders are better managed by Ayurveda medicine . Pravala panchamrita rasa is one such rasashastriya formulation which is commonly used in pittaja disorders . Aim and Objective- To study and evaluate the clinical indications of Pravala panchamrita rasa in an experiencial and scientific view. Methods- Relevant refferences are taken from samhitas, sangraha granthas, contemporary literature, journals , internet, and from personal experiences. Discussion - Pravala panchamrita rasa is one such preparation which is commonly used in tha treatment of pittaja disorders. Urodaha, Udaradaha, Amlapitta , Gudadaha, bhrama and in udarashoola it is more effective . It not only releives signs and symptoms but also suppliments Calcium in the body. Conclusion- Pravala panchamrita rasa is a Kharaliya rasayana which is commonly used in pittaja disorders . There are least side effects even after its prolonged usage.